KONTRUKSI KOMUNIKASI ANTAR BUDAYA PADA KELUARGA BEDA ETNIS (ETNIK TORAJA DAN ETNIK BALI) DI KECAMATAN TOMONI TIMUR, KABUPETEN LUWU TIMUR, PROVINSI SULAWESI SELATAN - I WAYAN ASTRAGUNA (GANEC SWARA, 2022)
East Tomoni District, East Luwu Regency, South Sulawesi Province is an area with a pluralistic society, this plurality is characterized by the existence of community groups from various ethnicities, cultures, religions, customs and so on who live together for a long time and establish social relations The construction of intercultural communication in this study aims to find out how the process of intercultural communication occurs in families of different ethnicities and also how to establish harmonious family relationships. between these two ethnic groups so that it has a positive impact on building social harmony. This study was designed with a qualitative research with a phenomenological approach. Sources of data in this study are primary data and secondary data with data analysis with two data collection techniques, namely observation data and literature study. Data analysis in this study uses three stages, namely: reduction, data presentation, and conclusions. Checking the validity of the data is done by data triangulation. Based on the results obtained, it can be concluded that communication in different ethnic families can be built with intercultural communication. Because with intercultural communication, the two ethnically different families (Ethnic Bali and Ethnic Toraja) can understand each other's culture. In an effort to maintain inter-ethnic family harmony, several things need to be done including increasing inter-ethnic cultural education, increasing the intensity of inter-ethnic interaction and communication, assimilation, accommodation and also cultural adaptation